Estrategias de marketing en la Veterinaria Mi Pollito del cantón Babahoyo provincia de Los Ríos en el periodo 2023. - Diaz Muñoz, Javier Alexander (2024)
This study focused on analyzing effective marketing strategies adapted to the local market reality of the veterinary clinic ‘Mi Pollito’ in the Cantón Babahoyo, Province of Los Ríos. The issue reveals a lack of effective marketing strategies that limits customer attraction and retention, highlighting the need to improve these strategies to ensure the commercial success of the veterinary clinic and contribute to local development. The objective is to identify deficiencies in the current strategy, propose effective solutions, and assess their impact on commercial performance. The research lines cover the analysis of marketing techniques specific to agricultural products and their applicability in the local context. The conceptual framework focuses on marketing and sales theories adapted to the peculiarities of the agricultural sector, while the methodological framework employs a quantitative approach to collect data and analyze results. Through the survey conducted, it was determined that implementing strategies such as digital promotion, improving business visibility, and strengthening customer relationships can significantly improve the situation. Therefore, to achieve substantial improvement, it is crucial to adopt a comprehensive approach in the marketing strategy that encompasses both online promotion and personalized customer service. This study provides consistent information for future research and practices in the field of agricultural marketing.